AskMe! STA404 V2.0 / Norashikin Nasaruddin ... [et al.] - Nasaruddin, Norashikin; Abdul Rashid, Nurazlina; Kasim, Kartini; Zakaria, Shahida Farhan; Hassim, Hasniza; Mohd Helmi, Mohd Firdaus; Abd Rahim, Mas Aida (2020)
COVID-19 pandemic culminated in the closure of educational institutions all over the world. About 1.2 billion children worldwide are out of the field. As a result, education has dramatically changed with the distinctive emergence of e-learning, where teaching is carried out remotely and on digital platforms. It has been known that statistical application plays a critical role in supporting the process of online teaching and learning. AskMe!STA404 V2.0 is a platform for lecturers and students to connect inside and outside of classrooms regarding topics in Statistics for Business and Social Sciences. This application can save time and paper and make it easy to communicate important announcements to the forum page, to post notes or video lectures, distribute assignments and at the same time stay organized. Moreover, this application provides the students with a view to the collection of questions that have been answered according to topics in this subject. AskMe!STA404 V2.0 has made the learning process easier and more convenient because it is accessible from all computers, mobile phones and tablets.